Pyrolysis of walnut shell residues in a fixed bed reactor: Effects of process parameters, chemical and functional properties of bio-oil. Issue 4 (August 2021) - Shah, Mudasir Akbar; Khan, N.S.; Kumar, Vimal; Qurashi, Ahsanulhaq
Abstract: In the present work the products and characteristics of bio-yields obtained from pyrolysis of different types of walnut shells (WS) by using a fixed bed pyrolyzer. The different walnut shells considered are paper (PSW), thin (TSW), medium (MSW) and hard (HSW) shelled walnut. The biomass samples were pyrolyzed at various temperatures, particle sizes, heating and sweep gas flow rates. The results revealed that the maximum bio-oil 44.7, biochar 37.6 and gas 40.4 wt% yields have been obtained for HSW, MSW and HSW at a pyrolysis temperature of 550, 375 and 750 °C respectively at heating rate 0.33 K/sec, particle size 0.5–1.5 mm with swept gas flow rate 1.6 × 10 −6 m 3 /s. The higher heating value (HHV) of bio-oil obtained from different walnut shells are ranged from 26 to 27.3 MJ/kg. Comprehensive physiochemical characteristics such as density, viscosity, flash point, pour point and water content of bio-oils have been obtained. Chemical composition analysis of bio-oils revealed that the pyrolytic bio-oil composition is predominated by oxygenated compounds such as carbonyl, methoxy, phenols and carboxyl groups determined by GC-MS, FTIR, 1 H NMR and 13 C NMR. The pyrolysis gas mainly contained CH4 CO, H2, CO2, and light hydrocarbons. Based on these results and structural analysis of the bio-oil, it can be concluded that the bio-oil obtained from WS may be used as a feedstock for furnaces, as a fuel, as a lubricant after modifications and value-added products via pyrolysis. Highlights: Products and characteristics of bio-oil, bio-char and gas were determined and discussed. The highest bio-oil yield was observed at 550 0 C temperature from all walnut shell residues. Pyrolysis process parameters temperature, sweep gas flow rates, particle size etc discussed. Increasing nitrogen gas flow rates and heating rates are good for H/C molar ratios and pyrolysed. The maximum HHV (27.3 MJ kg−1) was obtained for bio-oil from hard walnut shell.